Advanced education and organizational culture theories: referents for a classroom observation model - Quesada Pita , Guadalupe de las Mercedes; Taño Hernández-Piloto , Herminia Carmen; Panesso Patiño , Vanessa (Revista Minerva, 2023)
Objective to socialize the classroom observation model to evaluate the pedagogical professional performance with impact on the quality of the teaching-learning process. Methods the general dialectical-materialistic method is applied with the methods of the theoretical and empirical levels. The historical-logical method supplies the record of the dimensions related to the conception and elaboration of the observation model. The systematization useful in the combination of the essentialities and regularities of the teaching-learning process, according to scientific-technical-methodological and ethical aspects. Results conception, design, and application of the observation model to class. The classroom observation model is a resource conceived by the center for the improvement of the pedagogical professional performance with greater scientific-technical-methodological and ethical rigor.
Keywords: Observation; observation guide; dimensions; professional performance